2008
DOI: 10.1177/1073191107307509
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Florida Cognitive Activities Scale in Older African Americans

Abstract: Substantial research effort has recently focused on the potential protective effect of cognitively demanding activities on cognitive decline in late life. A significant methodological issue in this effort has been the lack of consistency in approaches to the operational measurement of cognitive activity. In this study, data in support of the reliability and construct validity of the recently developed Florida Cognitive Activities Scale (FCAS) in a sample of 223 African American older adults are provided. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
2
18
0
Order By: Relevance
“…The activities reported by these participants were highly similar to those previously reported in studies examining engagement patterns in adulthood, with television watching, reading, socializing, and essential daily activities (e.g., preparing food) among those activities most frequently endorsed (e.g., Arbuckle, Gold, Chaikelson, & Lapidus, 1994; Dotson, Schinka, Brown, Mortimer, & Borenstein, 2008; Parisi, 2010; Salthouse, Berish, & Miles, 2002). A few differences were noted; specifically, individuals in the present study reported high levels of religious involvement, replicating other findings suggesting that African-Americans center many of their activities around religious involvement (e.g., Krause, 2006; Taylor, Chatters, McKeever Bullard, Wallace, & Jackson, 2009).…”
Section: Discussionsupporting
confidence: 74%
“…The activities reported by these participants were highly similar to those previously reported in studies examining engagement patterns in adulthood, with television watching, reading, socializing, and essential daily activities (e.g., preparing food) among those activities most frequently endorsed (e.g., Arbuckle, Gold, Chaikelson, & Lapidus, 1994; Dotson, Schinka, Brown, Mortimer, & Borenstein, 2008; Parisi, 2010; Salthouse, Berish, & Miles, 2002). A few differences were noted; specifically, individuals in the present study reported high levels of religious involvement, replicating other findings suggesting that African-Americans center many of their activities around religious involvement (e.g., Krause, 2006; Taylor, Chatters, McKeever Bullard, Wallace, & Jackson, 2009).…”
Section: Discussionsupporting
confidence: 74%
“…Internal consistency reliability of the Scale was Cronbach’s alpha from 0.65 to 0.79 in healthy elders and 0.68 among 223 African-American older adults. 75,76 Construct validity was supported by factor analysis and discriminant validity was supported by comparing scores of healthy elders and persons with neurological impairments. 75,76 In the current study, the Cronbach’s alpha reliability was 0.77 at baseline and 0.76 at 12 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies on the association between cognitive activity and cognitive function in non-demented older adults have been in predominantly non-Hispanic Whites (e.g., Hultsch et al, 1999; Verghese et al, 2003; Wang et al, 2002; Wilson et al, 2005), and a small number in primarily non-Hispanic Blacks (Barnes, Wilson, Mendes de Leon, & Bennett, 2006; Dotson, Schinka, Brown, Mortimer, & Borenstein, 2008). Studies in geographically defined biracial samples have found less frequent engagement in cognitive activity in Blacks than Whites (Wilson et al, 1999; Wilson, Bennett, et al, 2002), but similar associations of cognitive activity to cognitive decline (Wilson et al, 2003) and incident dementia (Wilson, Bennett, et al, 2002).…”
Section: Introductionmentioning
confidence: 99%